(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India has rich history of measuring political participation of women since its Independence, with more responsive data on women participation, better gender budget initiatives aim to move the country towards a gender equal society. The constitution of India on the principles of equality and guarantees equality before law and equal protection to all its citizens. It not only guarantees fundamental rights and freedoms, but also prohibits discrimination on the basis of religion, race, caste, sex and place of birth. However, these rights have remained de jure and have not been translated.